Pantoeaagglomerans an Agent to Remove Residual Copper from Aquaculture Activity - Tello-Reyes, M (Trans Tech Publications Ltd, 2014)
The adhesion of microorganisms to the floating cages in the aquaculture industry is currently controlled with copper as a biocide paints problem. The development of these activities has resulted in marine and freshwater sediments next to the culturecenters high levels of copper. Dueto these problems of environmental pollution, at present have been implemented new technologies of biological origin for the detoxification of ecosystems through the use of microorganisms (fungi, yeasts and bacteria). Therefore the main objective of this work is the search for marine microorganisms for the removal of copper. For this, samples were collected from marine sediment contaminated with copper Tenglo Channel (41 ° 29?23.59 ?S, 72 ° 58?06.70? W). Gram negative bacterium of marine sediment was isolatedin TSA medium supplemented with 7 mMCu (II), this strain was designated as LMAE-2. The phylogenetic analysis has a 97% similarity with Pantoeaagglomerans. The high resistance for copper was determined at 9 mM.Finally, the metal removal capacity of this bacterium was determinate in 11.6% by Atomic Absorption Spectrometry. These results suggest that marine bacteria could be a biologic model system for use in processes for removal this toxic metal. © (2014) Trans Tech Publications, Switzerland.